A broadband circularly polarized metasurface antenna for wearable applications. Issue 11 (1st August 2022) - Zhao, Chen; Li, Wenran; Wang, Yang; Liao, Xiaoyi
Abstract: In this paper, a broadband circularly polarized wearable antenna for wireless body area network (WBAN) communication is proposed. The antenna consists of 2 × 2 metasurface unit cells with 12 parasitic rectangular metal patches. A driven patch with an unsymmetric U‐shaped slot is used to excite the proposed antenna. Flexible materials of felt and polyimide are used for wearable requirement. The 3 dB axial ratio (AR) bandwidth is greatly improved with the help of parasitic patches. The measured results show a very wide impedance bandwidth from 4.30 to 8.46 GHz (64.4%) and a 3 dB AR bandwidth from 5.39 to 8.46 GHz (44.3%). Besides, a quite stable gain of 7.8 ± 1 dBic is got from 5.02 to 8.18 GHz (56.9%). It is also proved with both simulation and measurement that the antenna has stable performance with structural deformation and loading of the human body. The specific absorption rate is also under the standard values. All these advantages of the proposed antenna make it a good candidate for WBAN applications.